ЭКОНОМИЧЕСКАЯ ТЕРМИНОЛОГИЯ В СОВРЕМЕННОМ КАЗАХСКОМ ЯЗЫКЕ: ФЕНОМЕНЫ ПОСТСОВЕТСКОГО ЯЗЫКОВОГО ПРОСТРАНСТВА - Pociechina, Helena; Musagułowa, Aida (Acta Neophilologica, 2013)
Set against the background of all the economic changes in the countries of the former Soviet Union, linguistic reforms play an important role. For over a hundred years the literary language of the Kazakhs has been shaped by the influences of Russian. Nowadays, when the independent Kazakhstan is developing its economy, sciences and technologies as well as international cooperation, it is the main task of linguists to create appropriate terminology. It is to be based on three sources: the present vocabulary, historical resources of the Kazakh language, and English loanwords. Such an approach is founded on the linguistic policy of President Nursultan Nazarbajev, which is aimed at introducing a three-language model of society development.